Improved calibration procedures and new standards for U–Pb and Th–Pb dating of Phanerozoic xenotime by ion microprobe - Fletcher, Ian; McNaughton, Neal; Aleinikoff, J.; Rasmussen, Birger; Kamo, S. (Elsevier Science BV, 2004)
Xenotime is a widely occurring mineral that is amenable to U–Pb and Th–Pb dating but often is found as micrometre-sized crystals that can only be dated by in situ microanalytical techniques. Determining accurate ages for Phanerozoic samples, and assessing concordance in older samples, requires accurate determination of Pb/U and Pb/Th; however, ion microprobe data for these ratios are affected by the highly variable trace element composition of xenotime. We have identified calibration procedures, including matrix corrections for the effects of the dominant trace elements U, Th and REE, that provide an accuracy of ~1% for Pb/U and <2% for Pb/Th. Several new standard samples are available that cover a range of compositions, permitting better matching of samples with standards as well as giving control of the matrix effects. However, no chemically homogeneous samples have been identified.